Reescritura y puesta en abismo del ménage à trois en Punto de referencia - Cuvardic García, Dorde (Káñina, 2013)
This article aims to identify the main procedures on both narrative and semantic levels operated in the rewriting ofPunto de referencia, contained as hypotext in the play premiered in the 80 ́s, and as hypertext in the novel published in2000. This rewrite was realized by Daniel Gallegos himself. Some excerpts from the play become in the novel a part ofthe screenplay that the main character has decided to film. The scenes featured in the script are used in the context of theproceedings of the setting of the mise en abyme: they reproduce the ménage à trois that takes place in the main action ofthe novel. In semantic terms there also operates a rewrite of the ménage à trois. In the play the male couple relationshipbecomes more fully developed, while in the novel the "tripartite" (two men and a woman) conflict is more important.